IMPLIKASI FINANCIAL TECHNOLOGY, LITERASI KEUANGAN DIMEDIASI OLEH DIGITAL MARKETING TERHADAP KINERJA KEUANGAN UMKM - Astri Yulidar Abbas, Muhammas; Wahyuti, Sri; Safrullah, Safrullah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This research aims to determine the direct effects that occur due to the existence of financial technology and financial literacy mediated by digital marketing on the financial performance of MSMEs in Samarinda City. This research uses quantitative descriptive research, and the nature of this research is explanatory research. The sample for this research is MSMEs in Samarinda City. The sampling technique uses a purposive sampling method. The data analysis used is SEM PLS (Partial Least Square) analysis. Primary data was obtained from distributing questionnaires with data collection techniques using questionnaires and documentation. The results of the research state that the relationship between fintech and positive financial performance has no significant effect, the relationship between financial literacy and positive financial performance has a significant effect, and digital marketing mediates fintech and financial literacy on financial performance positively and significantly. Digital marketing is 80% an influential and significant factor in financial performance, with 20% other variables.